The 9th Annual International Seminar on Trends in Science and Science Education (AISTSSE) 2022 : Development of Industrial-Based Research on Improving Research Innovation Strategy In Science and Science Education (Sciendo, 2023)
This is the ninth time we are hosting this seminar and we are proud to inform you that this seminar is an annual event in our calendar and has been held every year since 2014. This year, for the third year, we are holding it via Zoom meeting (online meeting) due to Covid-19 pandemic. We are inviting internationally recognized speakers from several countries to share their latest discoveries in the fields of Biology, Chemistry, Physics, Mathematics and Science Education. Well-known researchers in science and science education will share their experiences and knowledge so that we can stay up-to-date with the latest information. This is one of the goals of this seminar. As science researchers, we realize the importance of information exchange among us. The new information enlightens our minds and gives us ideas on what to do next in our research and how to do it. This new information often becomes the foundation for our next project in particular and sets the research trends for the upcoming year in general. Information exchange also keeps us updated, allowing us to give and receive suggestions and critiques that will lead to better results. Therefore, we need a forum where we can share and exchange information. Seminars, conferences, and other scientific gatherings are the media through which we can do this. Organizer Faculty of Mathematics and Natural Sciences of Universitas Negeri Medan Where Web Seminar via Zoom Meeting When Tuesday, 8th November 2022 Theme The development of industrial-based research in science and science education to improve research innovation strategy Topics: AISTSSE-2020 included following topics: 1. Mathematics Science 2. Mathematics Education 3. Physics Science 4. Physics Education 5. Biology Science 6. Biology Education 7. Chemistry Science 8. Chemistry Education 9. Computer Science 10.Science Education Scientific Committee 1. Prof. Dr. Syawal Gultom, M.Pd, Universitas Negeri Medan (Indonesia) 2. Prof. Dr. Marleen Kamperman, University of Groningen (Netherland) 3. Prof. Manihar Situmorang, M.Sc., Ph.D, Universitas Negeri Medan (Indonesia) 4. Prof. Tsunenori Mine, School of Engineering, Department of Electrical Engineering and Computer Science, Kyushu University (Japan) 5. Prof. Dian Armanto, M.Pd, Universitas Negeri Medan (Indonesia) 6. Prof. Dr. Herbert Sipahutar, M.Sc, Universitas Negeri Medan (Indonesia) 7. Prof. Abedel Karrem Nasser M Alomari Department of Mathematics, Faculty of Science, Yarmouk University (Jordan) 8. Prof. Dr. Bornok Sinaga, M.Pd, Universitas Negeri Medan (Indonesia) 9. Prof. Dr. Muhammad Sattar Rasul Universitas Kebangsaan Malaysia, (Malaysia) 10. Prof. Motlan, M.Sc., Ph.D, Universitas Negeri Medan (Indonesia) 11. Prof. Dr. Asmin, M.Pd, Universitas Negeri Medan (Indonesia) 12. Prof. Dr. Fauziyah Harahap, M.Si, Universitas Negeri Medan (Indonesia) 13. Prof. Dr. Mukhtar, M.Pd, Universitas Negeri Medan (Indonesia) 14. Prof. Dr. Pargaulan Siagian, M.Pd, Universitas Negeri Medan (Indonesia) 15. Prof. Dr. Sahat Saragih, M.Pd, Universitas Negeri Medan (Indonesia) 16. Prof. Dr. Edi Syahputra, M.Pd, Universitas Negeri Medan (Indonesia) 17. Prof. Dr. Hasratuddin, M.Pd, Universitas Negeri Medan (Indonesia) 18. Prof. Dr. Ramlan Silaban, M.Si, Universitas Negeri Medan (Indonesia) 19. Prof. Dr. Retno Dwi Suyanti, M.Si, Universitas Negeri Medan (Indonesia) 20. Prof. Dr. Nurdin Bukit, M.Si, Universitas Negeri Medan (Indonesia) 21. Prof. Dr. Sahyar, M.